ADVERTISING IN THE BOOK MARKET - VAIŠVILIENĖ, ALINA (Knygotyra, 2015)
The article considers advertising and book market interactions: analysis of advertising in publishing research and in practice. It also reviews specific book market characteristics, advertising effects at the socio-cultural level, the book advertising situation in other countries. Analysis of book advertising practice has showed that book advertising is the bestseller and brand-building measure. Although the book has a short life cycle, its advertising aims at the formation of long-term market response. The author has found that the structure of advertising and its effect depend on the book market characteristics; however, the process of advertising also changes the book market by developing new processes and events beyond business boundaries: it affects the demand for books, product diversity, the process of book publishing and bookselling, etc. A study of advertising and book market relations unveils the importance of independent book evaluation. The high advertising noise, a wide and dispersed audience, competition from consumer goods ads undermines the role and influence of advertising on book viability: ads often are perceived passively or go unnoticed.